Music therapy and the work of the music therapist (Journal of Parents and Teachers, 2014)
Music is a language that everyone understands. It is a natural form of communication that can be used for growth. Although the technique of music therapy has only recently appeared, it is already finding its way into schools, nursing homes and hospitals among others. The function is not to create aesthetically correct music, music is used as a therapeutic medium and its benefits will depend on the planning of the session. In turn, each session will depend on the patient's problem; the five basic tendencies are explained. The success of music therapy lies in the fact that it is a language that everyone understands. The methodology in music therapy consists of the diagnostic process and the therapeutic process.
Keywords: music therapy; therapy; mental care; music